Assessment of Dentofacial Characteristics and Pharyngeal Airway in Children with Class II Malocclusion and Mouth Breathing - Shetty, Swathi; Shetty, Vabitha; Bhandary, Meghna (Journal of Health and Allied Sciences NU, 2022)
Background In growing patients with skeletal discrepancies, early diagnosis, evidence-based explanation of etiology, and assessment of functional factors can be vital for the restoration of normal craniofacial growth and the stability of treatment needs.Aims The aim of the study was to assess dentofacial characteristics as well as upper and lower pharyngeal airway in children with skeletal class II malocclusion with mouth breathing, and to investigate possible significant relationships and correlations among the studied cephalometric variables and the airway morphology in these children.Materials and Methods Sixty untreated children, aged 9 to 13 years, were divided into three groups according to clinical findings and cephalometric analysis of dentofacial characteristics as well as the presence of mouth breathing habit: Group I (20 children with normal jaw relation/class I), Group II (20 children with skeletal class II), and Group III (20 children with skeletal class II with confirmed mouth breathing habit). Cephalometric variables and upper/lower airway widths were recorded. Intergroup comparison of all measurements was performed by post hoc Tukey test, and Pearson's correlation was used to determine the correlation among the variables.Results Significant changes existed in more than half of the dentofacial measurements among the three groups. Significantly greater skeletal anteroposterior jaw discrepancy and mandibular retrognathism were found in both groups II and III as determined by specific anteroposterior determinants. Children in group III showed significantly increased angle between Sella-Nasion and mandibular plane (SN-MP) angle, y-axis, and a vertical growth pattern. Significant increases in dental measurements, namely upper incisor to Nasion- point A (NA), lower incisor to Nasion - point B (NB), and overjet, were found in group II and group III, while overbite showed a significant decrease. Upper pharyngeal airway width was found to be significantly decreased in group III followed by a smaller though significant decrease in group II. No significant differences were found in lower pharyngeal airway width between the groups. There were statistically significant dentofacial characteristics that showed fair to good correlation with the upper airway width.Conclusion Children with skeletal class II malocclusion with and without mouth breathing showed significant differences in dentofacial measurements and a significantly narrower upper pharyngeal airway as compared with children with normal jaw/class I relation.
Keywords: mouth breathing; skeletal class II malocclusion; pharyngeal airway